Rettet Kurzarbeit in Rezessionen Arbeitsplätze? - Britta Gehrke; Brigitte Hochmuth (Wirtschaft und Gesellschaft (WuG), 2017)
Short-time work (STW) allows firms that face a temporary shortfall of demand to reduce the working hours of their employees. The employees are partly compensated by the government for their net wage loss. As such, STW is a targeted labor market policy with the aim to enable firms to adjust their labor input without dismissing workers. During the Great Recession the majority of OECD countries used STW schemes, however, countries differ widely in their STW usage. The share of short-time workers in Germany, for example, was five times higher compared to Austria. In this article, we present the results of our current research project on STW. We disentangle discretionary and rule-based STW policy and focus on possible time-varying effects of ad-hoc policy changes. Our results for Germany show that the employment effects depend crucially on the state of the business cycle: In deep recessions, discretionary STW policy stabilizes employment, whereas in normal times and expansions the effects are less clear and may even turn negative. We find that the deeper the recession, the more jobs can be saved with discretionary STW policy. An analysis of the underlying mechanism illustrates that the employment effects are caused by a significant reduction of lay-offs.
Keywords: 330; Kurzarbeit; Arbeitsplatzsicherung